Recent trends in the research on national innovation systems - Markus Balzat; Horst Hanusch (Universität Augsburg, Institut für Volkswirtschaftslehre, 2003)
In this paper, we give an overview on recent developments in the research on national innovation systems (NIS). Essentially, we identify three development lines of the concept. These are policy-oriented studies that frequently combine the NIS approach with the terminology of corporate benchmarking, contributions to formalize the concept of NIS through descriptive or analytical models, and NIS studies of countries beyond the group of highly industrialized economies. It follows from the analysis of these research trends that the concept has developed in distinctive directions. In international comparisons of innovation systems, heterogeneity in the structure of the systems is only marginally taken into account, an aspect that may reduce the explanatory power of such system-level comparisons. Contrary to this, historically grown organizational and institutional structures are extensively described and considered in NIS tudies of industrializing countries, a characteristic which ties up with early studies of national innovation systems.
urn:nbn:de:bvb:384-opus4-712030
Keywords: P51; O50; O31; O11; 330; innovation; national innovation systems; comparative studies; Innovation; Innovationspolitik; Wirtschaftsforschung; international; Vergleich